EFEKTIVITAS VIDEO TUTORIAL SEBAGAI MEDIA PENGEMBANGAN PEMBELAJARAN RODA GIGI LURUS PADA MATA PELAJARAN TEKNIK PEMESINAN FRAIS DI SMK DI JAKARTA - Sugeng Priyanto (LPPM Institut Pendidikan Nusantara Global, 2024)
Learning media is one of the important factors in improving the effectiveness of learning as it can help increase student engagement and facilitate access to course materials. The selection of video media in learning media can provide various benefits for students, such as helping to reinforce learned concepts, providing interesting visual examples, and enhancing student motivation. The development of video tutorial media for the production of straight gears in the subject of milling machining techniques at SMKN 52 Jakarta uses the Research and Development (R&D) research method with the ADDIE development model. The results of the feasibility test of learning media through video tutorials obtained a